Semantic verbal fluency impairment is detectable in patients with subjective cognitive decline. Issue 5 (3rd September 2018) - Nikolai, Tomas; Bezdicek, Ondrej; Markova, Hana; Stepankova, Hana; Michalec, Jiri; Kopecek, Miloslav; Dokoupilova, Monika; Hort, Jakub; Vyhnalek, Martin
ABSTRACT: Patients with subjective cognitive decline (SCD) are at higher risk for conversion to dementia due to Alzheimer's disease (AD). Semantic verbal fluency (SVF) seems to be impaired in the early stages of AD. The goal of the present study was to identify the discriminative potential of verbal fluency (VF) in patients with SCD to show if very early signs of cognitive decline may be detected in SCD. We examined 93 normal controls (NC) and 61 participants with SCD. Each participant was administered a comprehensive neuropsychological battery. All participants underwent tests of VF: phonemic verbal fluency (PVF), letters K and P and SVF (animals and vegetables categories). In addition to the total score, two 30-second intervals, and clustering and switching indices in SVF were evaluated. SCD generated fewer words in the total score and 30- to 60-second interval in vegetables category and they performed more switches in animals category. There was no significant difference between the SCD and the NC groups in all other VF measures. Quantitative measures of SVF (a decreased number of vegetables) as well as qualitative measures were detected in SCD group and could be considered as an early neuropsychological marker of subtle cognitive impairment.